IMPROVING STUDENTS’ LISTENING SKILL BY USING ANIMATION VIDEOS THROUGH SENTENCE COMPLETION AT SMPN 1 BANDAR BARU - Rini Susiani; Farizawati Farizawati; Ema Dauyah; Kana Riska (Jurnal Dedikasi Pendidikan, 2020)
This study aimed to find out the effect of using animation videos through sentence completion in teaching listening. The method used in this study was an experimental approach in the form of one group pre test- post test design. The study was conducted at SMPN 1 Bandar Baru with a number of samples were 44 students randomly selected. To obtained the data, the researcher gave the test. the result of pre test was 470, and post test was 650, the mean score (  was 8,18. Furthermore in experimental class, the result of pre test was 680 and post test was 1670, the mean score ( was 45. The result both of the classes was 6,56. Furthermore, significant level α= 0,05, degrees of freedom (d.f)=(  = (42 to obtained by interpolation . It was obtained . In other words, it indicates that the students who were taught using animation videos through sentence completion achieved better result in listening than the students who were taught using non animation videos. Finally, it can be inferred that the use of animation videos through sentence completion in teaching listening can improve students’ listening ability in SMPN 1 Bandar Baru.